A surrogate model for estimating uncertainty in marine riser fatigue damage resulting from vortex-induced vibration. (1st March 2022) - Lim, HyeongUk; Manuel, Lance; Low, Ying Min; Srinil, Narakorn
Abstract: Of interest in this work is the quantification of uncertainty in fatigue damage of a top-tensioned riser (TTR) resulting from vortex-induced vibration (VIV). Using a distributed wake oscillator model in time-domain simulations of a riser in uniform current, followed by rainflow cycle-counting, fatigue damage is computed. A polynomial chaos expansion (PCE) representation of damage is derived that treats three wake oscillator model variables as direct stochastic input: (i) motion amplitude; (ii) the ratio of vortex-shedding frequency to riser natural frequency; and (iii) current velocity. Damage at different locations along the selected riser is assessed. Damage predictions, obtained using the efficient PCE framework, are compared against the more computationally expensive alternative that involves Monte Carlo Simulation (MCS). This study suggests that PCE offers a tractable, versatile and accurate option for VIV-related fatigue damage prediction. Highlights: Surrogate models are developed for riser fatigue damage prediction. Polynomial chaos expansion is used to account for uncertainty in fatigue damage. Accuracy is assessed by comparison with Monte Carlo simulation results. Damage at different locations is studied for validation of the proposed method.